Increasing the Yield of Green Mustard (Brassica juncea L.) by Using a Dose of Goat Manure Tricho POC Fertiliser (Agrikan Jurnal Agribisnis Perikanan, 2023)
One type of vegetable commodity is very popular with the people of Indonesia, namely mustard greens (Brassica juncea L.) because it has a number of minerals, vitamins, carbohydrates and vegetable proteins that are beneficial to the health of the human body. Green mustard production is relatively good and has a relatively short harvest age of 40-50 days, so it is very feasible to be cultivated in a competitive cultivation system because it has good market opportunities so that it can provide adequate benefits in increasing farmers' income. The research was conducted in July-September 2023 using RAK with 5 treatment levels of goat manure Tricho POC organic fertiliser dosage. K0 = without using Tricho POC goat manure fertiliser (control), K1 = Tricho POC goat manure 5 ml/litre water, K2 = Tricho POC goat manure 10 ml/litre water, K3 = Tricho POC goat manure 15 ml/litre water, K4 = Tricho POC goat manure 20 ml/litre water. A dose of 20 ml/litre of tricho POC goat manure water, is the best dose treatment in increasing the growth and yield of green mustard plants.
Keywords: Trichoderma; POC; Mustard Greens.